Clonal haematopoiesis in chronic ischaemic heart failure: prognostic role of clone size for DNMT3A- and TET2-driver gene mutations. (26th November 2020) - Assmus, Birgit; Cremer, Sebastian; Kirschbaum, Klara; Culmann, David; Kiefer, Katharina; Dorsheimer, Lena; Rasper, Tina; Abou-El-Ardat, Khalil; Herrmann, Eva; Berkowitsch, Alexander; Hoffmann, Jedrzej; Seeger, Florian; et al.
Abstract: Aims: Somatic mutations of the epigenetic regulators DNMT3A and TET2 causing clonal expansion of haematopoietic cells (clonal haematopoiesis; CH) were shown to be associated with poor prognosis in chronic ischaemic heart failure (CHF). The aim of our analysis was to define a threshold of variant allele frequency (VAF) for the prognostic significance of CH in CHF. Methods and results: We analysed bone marrow and peripheral blood-derived cells from 419 patients with CHF by error-corrected amplicon sequencing. Cut-off VAFs were optimized by maximizing sensitivity plus specificity from a time-dependent receiver operating characteristic (ROC) curve analysis from censored data. 56.2% of patients were carriers of a DNMT3A - ( N  = 173) or a TET2 - ( N  = 113) mutation with a VAF >0.5%, with 59 patients harbouring mutations in both genes. Survival ROC analyses revealed an optimized cut-off value of 0.73% for TET2 - and 1.15% for DNMT3A -CH-driver mutations. Five-year-mortality was 18% in patients without any detected DNMT3A - or TET2 mutation (VAF < 0.5%), 29% with only one DNMT3A - or TET2 -CH-driver mutations above the respective cut-off level and 42% in patients harbouring both DNMT3A - and TET2 -CH-driver mutations above the respective cut-off levels. In carriers of a DNMT3A mutation with VAF ≥ 1.15%, 5-year mortality was 31%, compared with 18% mortality in those with VAF < 1.15% ( P  = 0.048). Likewise, in patients with TET2 mutations, 5-year mortality was 32% with VAF ≥ 0.73%, compared with 19% mortality with VAF < 0.73% ( P  = 0.029). Conclusion: The present study defines novel threshold levels for clone size caused by acquired somatic mutations in the CH-driver genes DNMT3A and TET2 that are associated with worse outcome in patients with CHF. Graphical Abstract: